2005
DOI: 10.1210/me.2004-0181
|View full text |Cite
|
Sign up to set email alerts
|

9-cis-Retinoic Acid Inhibits Androgen Receptor Activity through Activation of Retinoid X Receptor

Abstract: Although the retinoic X receptor (RXR) forms heterodimers with many members of the estrogen receptor subfamily, the interaction between RXR and the members of the glucocorticoid receptor subfamily remains unclear. Here we show that the RXR can form a heterodimer with the androgen receptor (AR) under in vitro and in vivo conditions. Functional analyses further demonstrated that the AR, in the presence or absence of androgen, can function as a repressor to suppress RXR target genes, thereby preventing the RXR bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Beside the fact that Werner and DeLuca (2001) question the role of 9-cis RA as the physiological RXR ligand because the compound could not be identified in any tissue of analyzed rats, it has been shown for the fiddler crab Uca pugilator that a simultaneous expression and association of the RXR and the ecdysteroid receptor (EcR) is required to bind to responsive DNA elements (Durica et al 2002). Other receptors, including the AR, are also reported to form heterodimers with the RXR (Chuang et al 2005). According to these results, the AR and RXR affect their transcription mutually and it cannot be excluded that RXR activation might produce androgenic but also antiandrogenic effects by this mechanism.…”
Section: Neuropeptide Hypothesismentioning
confidence: 99%
“…Beside the fact that Werner and DeLuca (2001) question the role of 9-cis RA as the physiological RXR ligand because the compound could not be identified in any tissue of analyzed rats, it has been shown for the fiddler crab Uca pugilator that a simultaneous expression and association of the RXR and the ecdysteroid receptor (EcR) is required to bind to responsive DNA elements (Durica et al 2002). Other receptors, including the AR, are also reported to form heterodimers with the RXR (Chuang et al 2005). According to these results, the AR and RXR affect their transcription mutually and it cannot be excluded that RXR activation might produce androgenic but also antiandrogenic effects by this mechanism.…”
Section: Neuropeptide Hypothesismentioning
confidence: 99%
“…However, localization of AR to specific genomic sites is clearly more complex than simple sequence recognition. Similarly, AR can regulate transcription by distinct mechanisms; depending on cell or gene context, AR can activate or repress transcription, can functionally interact with other transcriptional regulators (Murtha et al 1997;Sato et al 1997) or with other intracellular receptors (Chen et al 1997;Lee et al 1999;Panet-Raymond et al 2000;Chuang et al 2005). Hormone response element (HRE) organization is likely a major determinant of receptor specificity and coregulator recruitment in a given chromosomal context (Lefstin and Yamamoto 1998).…”
mentioning
confidence: 99%
“…7); however, 9-cis RA for RXR ligand significantly inhibited both p120α and p120β tranactivation induced by DHT. It should be noted that previous studies have shown that liganded RXR can function as a repressor to suppress the AR target gene [23]. The decreasing p120β function in the presence of 9-cis RA may be due to this direct proteinprotein interaction between RXR and AR.…”
Section: Expression Of P120α and β In Prostate Diseases And Cultured mentioning
confidence: 87%